THE INTERPLAY OF HISTORY AND ECONOMICS: LESSONS FROM THE PAST - Shabir Ahmad Lone; S. Nazeemunnisa Begum; R. Abida Begum (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
History and economics are closely related. Because a man's actions in society are closely related to economic issues, a historian of any age must have at least a basic understanding of economics. Because they can frame questions about complex economic, social, and political issues and look for patterns and outcomes of prior episodes, economic historians are frequently in a good position to reply to questions about current global economic trends and crises. The current study emphasises the relationship between history and economics in social science and their significance in the contemporary environment.